Evolutionary dynamics and recombination patterns in begomoviruses infecting Abelmoschus esculentus: A phylogenetic and population structure analysis - Chahat, S; Akshu, J; Rahul, K; Yogesh, K (Plant Science Today, 2026)
Okra (Abelmoschus esculentus (L.) Moench) is a major vegetable crop cultivated globally, particularly in India and Nigeria, but it is highly susceptible to begomovirus infections transmitted by the whitefly (Bemisia tabaci). The predominant virus, Bhendi yellow vein mosaic virus (BYVMV), along with related viruses such as Bhendi yellow vein India virus (BYVIV), Tomato leaf curl New Delhi virus (ToLCNDV), Okra leaf curl virus (OkLCuV) and Okra mosaic virus (OMV), causes severe yield losses. This study examines the genetic diversity and recombination patterns of begomoviruses infecting okra using 94 viral genome sequences (DNA-A, DNA-B and betasatellites) retrieved from public databases. Phylogenetic analysis revealed distinct viral clades, while nucleotide substitution analysis showed that transitions occurred more frequently than transversions. Recombination analysis identified several breakpoints in the replication (Rep) and coat protein (CP) genes, with 29 and 11 breakpoints, respectively. Genetic diversity parameters showed high variation, with nucleotide diversity values of 0.13025 for DNA-A, 0.20899 for DNA-B and 0.10672 for betasatellites. The AC1 gene exhibited the highest mutation rate. Haplotype analysis identified 50 haplotypes for DNA-A, 8 for DNA-B and 36 for betasatellites, with DNA-A and betasatellites showing nearly complete haplotype diversity. Neutrality tests suggested selective pressure on the virus populations, possibly due to population expansion or purifying selection. These findings enhance understanding of begomovirus evolution and underscore the need for continuous monitoring and management of viral diseases in okra cultivation.